Kinetic Analysis of Rice Husk Pyrolysis Using Kissinger-Akahira-Sunose (KAS) Method - Jawad, Zeinab (Elsevier BV, 2016)
The pyrolysis of rice husk is studied using thermogravimetric analysis (TGA) equipment. The present study investigates the thermal degradation behavior and determination of the kinetic parameter such as activation energy, E using Kissinger-Akahira-Sunose (KAS) method. The kinetic data is produced based on first order rate of reaction. In the present study, the experiments are conducted at different heating rates of 10, 20, 30, and 50 K/min at non-isothermal condition with carrier nitrogen gas flowrate of 100 mL/min. The temperature range studied is 323-1173 K. Results showed that the maximum degradation rate of rice husk increases from 4.42 to 21.87 wt%/min as heating rate increases from 10 to 50 K/min. In addition, the predicted E values ranged from 48.64 to 54.21 kJ/mol meanwhile the average E values achieved is 51.19 kJ/mol in the range of heating rates studied using KAS method.